Pemanfaatan Tepung Pisang Kepok dan Tepung Jagung dalam Pembuatan Kukis - Suryani, Suryani; Fitriani, Shanti; Ali, Akhyar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Kepok banana flour and corn flour can be used as ingredients in cookies. This research aimed to know the best formulations of kepok banana flour and corn flour of the quality of cookies. Design of the research was using a Completely Randomized Design Experimentfor 5 treatments and 3 replications.Treatments of kepok banana flour and corn flour were 100% : 0%, 75% : 25%, 50% : 50%, 25% : 75%, and 0% : 100%.The data obtained were analyzed statistically using Analysis of Variance (ANOVA) and Duncan’s New Multiple Range Test (DNMRT) at 5% level. The results showed that the ratio of kepok banana flour and corn flour significantly affected moisture, ash, protein, fat, carbohydrate contents and the sensory parameters. The best treatment of cookies from this research was 25% kepok banana flour : 75% corn flourwith moisture content 4.70%, ash 2.44%, protein 12.27%, fat 7.00%, and carbohydrate 73.57%.The result of descriptive test showed that cookies has yellow colour (3.10), flavour between banana and corn (3.13), taste between banana and corn (3.17). Overall assessment of hedonic test of cookies was liked by the panelist (1.93).Keywords: cookies, kepok banana, corn flour.